Evaluation on the Implementation of the COIS Values on the Teachers of Yayasan Penyelenggaraan Ilahi Indonesia, Semarang - Murwati Murwati; Agatha Ferijani (Journal of Management and Business Environment (JMBE), 2020)
Strong personal traits such as reliable, discipline, devoted believer, high responsibility, willing to sacrifice, and put others needs above his/her own needs, are the personal traits that can build a prosperous society and a more developed country. It also can be said that the quality of someone is not merely measured from IQ (intelligence), but also from EQ (the growing traits). The real education must cover the formation of the whole humanity. The important component of an education institution is teachers. Thus, Yayasan Penyelenggaraan Ilahi Indonesia (YPII) with their vision and missions has formulated some traits (smart, authentic, faith to the Divine’s courtesy, and solider or COIS) that must be embraced by the teachers of YPII  in order to be able to form good characters of the students thoroughly. This is the reason for evaluation of the implementation of the COIS values on the teachers of YPII. The research used qualitative approach using Focus Group Discussion (FGD) to gather data. Further evaluation on the implementation of the COIS values was to explore the factors supported or obstructed the implementation of COIS values. The research concluded that the implementation of COIS values in the teachers of YPII Semarang is not good. The reason is lack of continuous guidance and coaching. Teacher awareness on their role as a role model for students develops.